CARNAVAL EM JUIZ DE FORA: IDENTIDADE COMUNITÁRIA OU PRODUTO DA INDÚSTRIA CULTURAL? - Moreira, Arthur Barroso (2008)
This research is regarding the influences of the cultural industry on the formation of the identity in the Schools of Samba in Juiz de Fora, the transformations introduced in these clubs through the mass medias to long them years and the way for which the sambistas of Juiz de Fora make the adjust interpretation and assimilate the information of the cultural industry. The performance of the local medias front to the carnival. The work was divided in three stages: bibliographical research; accomplishment of a diagnosis from interviews halfstructuralized with the involved with Schools of Samba or historical expert people for the official parades of carnival in Juiz de Fora; and the qualitative analysis of the collected data. It was arisen historical trajectory of the Schools of Samba of Juiz de Fora and its points of contact with the Schools of Samba of Rio De Janeiro, beyond if to search to understand which have is the perception that the people from Juiz de Fora on the local parade. The information had been worked under the point of view of the Critical Theory, of the philosophical proposals of Michel Foucault, of the balances on the society of the spectacle. The work demonstrates that the main concern of the Schools of Samba of Juiz de Fora is with the accomplishment of a parade that if fits in the standards demanded for the cultural industry, consequently the spectacle around the party was changedded into a form of social control, eliminating the liberality and the trespass that traditionally are associates to the carnival.(AU)